Overview of Health Program Innovation “Fun For Mom” - Akila Labiba; Asmaripa Ainy (poltekkes kemenkes mataram, 2021)
Maternal and child health is an important concern for all nations in the world including Indonesia. “Fun For Mom” is an innovation program at Sako Public Health Center in Palembang for increasing the knowledge of mothers regarding breastfeeding practice, complementary feeding, and maternal health during pregnancy and breastfeeding period. This study describes the Fun for Mom program at Sako Public Health Center in Palembang. This was a qualitative study that involved the analysis of data collected from in-depth interviews, documents review, and observations to describe the Fun for Mom program using the RE-AIM framework at Sako Public Health Center in Palembang. The purposive sampling technique has been applied and twelve interviews were conducted with a Head of Sako Public Health Center, a Program Manager, two Program Implementers, three Cadres, and five Program Participants. RE-AIM framework is a multi-attribute model with five dimensions: reach, effectiveness, adoption, implementation, and maintenance. According to this framework, the findings illustrated that around ten pregnant or breastfeeding mothers participated in each activity session. Exclusive breastfeeding increased after a year of its implementation from 2017 to 2018. Mothers easily understand the information given because of the use of game media in this program. All information is conveyed in simple language and can be applied in daily childcare. Health operational assistance (it is called BOK) is used to fund this program. Other financial supports are needed for the sustainability of the program. The Fun for Mom program is feasible as a community empowerment effort in a health center setting and can be developed further.